Resistance to KRASG12C Inhibitors in Non-Small Cell Lung Cancer - Blaquier, Juan Bautista; Cardona, Andrés Felipe; Recondo, Gonzalo (Frontiers in Oncology, 2021)
KRAS mutations are one of the most prevalent oncogenic alterations in cancer. Until recently, drug development targeting KRAS did not convey clinical benefits to patients. Specific KRASG12C inhibitors, such as sotorasib and adagrasib, have been designed to bind to the protein’s mutant structure and block KRASG12C in its GDP-bound inactive state. Phase 1/2 trials have shown promising anti-tumor activity, especially in pretreated non-small cell lung cancer patients. As expected, both primary and secondary resistance to KRASG12C inhibitors invariably occurs, and molecular mechanisms have been characterized in pre-clinical models and patients. Several mechanisms such as tyrosine kinase receptors (RTKs) mediated feedback reactivation of ERK-dependent signaling can result in intrinsic resistance to KRAS target therapy. Acquired resistance to KRASG12C inhibitors include novel KRAS mutations such as Y96D/C and other RAS-MAPK effector protein mutations. This review focuses on the intrinsic and acquired mechanisms of resistance to KRASG12C inhibitors in KRASG12C mutant non-small cell lung cancer and the potential clinical strategies to overcome or prevent it.